Suffering of the Serbs in Prizrenski Podgor County in 1941 - Virijević, Vladan A. (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
This paper reports on the suffering of the Serbian population in Prizrenski Podgor County in Metohija during the April War in 1941 following the first months of the occupation of the Kingdom of Yugoslavia. The oppressors were the local Arbanasi who—by means of direct horror such as murders, wounding, robbery, beating, arson, and the like—intended to banish Serbian citizens, primarily the ones who settled there between the two world wars within the state project of agrarian reforms and colonization. The remnants of the demolished households bear witness to the prosecution of the colonists and the meticulous ethnic cleansing. In addition, the local Arbanasi chiefs claimed the cattle and other moveable property. The victims ran for their lives trying to reach the territory of Serbia, which was under German control, attempting to return to the places where they lived before colonization. They testified to the suffering and terror they were exposed to, which is the heuristic basis of this paper. Unfortunately, there are no precise data concerning the victims and the magnitude of their suffering. This paper is a modest contribution to the further study of this issue.